ANALISIS EFISIENSI BIAYA PRODUKSI DENGAN PENGGUNAAN BIAYA STANDAR DALAM MENINGKATKAN RASIO NET PROFIT MARGIN (STUDI EMPIRIS PADA UMKM DENDENG SAPI DI BANDA ACEH) - OI Sarah Magfirah B; Yulia Fitri (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpose of this research is to analyze the efficiency of production cost with the use of standard costing. To see if there are some differences between the application of the standar costing and actual costing. Futhermore, this research also seek the option value of the net profit margin ratio in MSMEs of dendeng sapi in Banda Aceh. This research use descriptive statistical analysis to analyze the data. Population in this research are MSMEs listed in Dinas Koperasi dan UMKM Kota Banda Aceh. Based on certain criterias, there are 3 MSMEs as the samples of the research. The research show that standard costing can efficiently the production costs, the difference between the standard costing and the actual production costs that occur is favourable. Based on the results of correlation test there is positive significant correlation between the efficiency of production costs and net profit margin